Specific RAPD frafments related with sex type in Salacca (Salacca edulis L.) - Gustian and Jamsari, Ediwirman, Irfan Suliansyah, (International Journal of Agricultural Sciences, 2015)
Salacca (Salacca edulis L.) is a tropical plant with a high economic value. The sexes of salacca can be grouped as dioecious, monoecious, dan hermaphrodite. Farmer's success in cultivation is especially determined by the male to female ratio. The present ratio of male and female plants is 1:4. Determining sex based on morphological characteristics is not effective and difficult for young plants (seedlings), also to lysozim marker and chromosome. Marker Assisted Selection is a strategy to determine sex using a marker. Random Amplifed Polymorfism DNA (RAPD) is an amplification technique that uses markers. Of 305 primers tested, 4 primers, OPO-17 produced 297 bp product, OPAP-20 produced 554 bp as the specific fragment for the female and UBC-454 produced 934 bp as the specific fragment for the female and UBC-454 produced 946 bp as male, primer UBC-78 with the size of fragment 562 bp as the specific fragment for the female.